A survey of semi-active control with MR dampers - Braz-César, M.T. (2014)
The present work describes part of the R&D on using a semi-active structural control technique in a civ il engineering experimental model frame equipped with a MR damper, developed within COVICOCEPAD project approved in the framework of Eurocores prog ram S3T. Some results are provided associated with the calibration of a magneto-rheological (MR) damper at FEUP (Faculdade de Engenharia da Universidade do Porto) as well as on the experiment al modal identification of the dynamic properties o f a small-scale metallic frame, with and without the in clusion of a specific MR device. Some numerical results of the controlled frame under simulated ear thquakes are given, to be later compared with the experimental results of such frame installed in a Q uanser shaking table.